Bolhas racionais nos setores da b3 e eleição para presidente do Brasil de 2022 - Ribeiro, Tomás Nogueira (Universidade Federal de São Carlos, 2023)
A presidential election process can generate rational expectations of a ‘risk premium’ among investors, with a speculative bias due to political uncertainty, allowing for the occurrence of explosive behavior in stock prices. In this study, stock prices were used at 5-minute intraday intervals to identify and date episodes of rational bubbles (explosive dynamics) in the sectors of B3 (Brazilian Stock Exchange and Over-the-Counter Market) throughout the Brazilian electoral process of 2022: comprising between the 5th business day after the start of electoral propaganda (08/23/2022) until the 15th business day after the second round (11/18/2022), totaling 60 trading sessions. To this end, the Generalized Supremum Augmented Dickey-Fuller test was applied in a panel configuration (Panel GSADF), with each B3 sector being a data panel. The following question was sought to be answered: during the Brazilian electoral period of 2022, were there rational bubbles in the B3 sectors? With the Panel GSADF test methodology, it was possible to detect multiple bubble episodes in the Oil, Gas and Biofuel (2 episodes), Health (2 episodes) and Information Technology (5 episodes) sectors. November 16th presented bubble episodes in these three sectors, with the Health sector having the longest explosive behavior. The studies and results presented in this work may be useful for theoretical and empirical researchers, economic authorities and private sector agents in order to become aware of mechanisms to identify bubbles in financial markets and measure their extensions.
Rational bubbles in the b3 sectors and the 2022 brazilian presidential election
Keywords: Painel GSADF; Exuber; Bolhas Racionais; GSADF Panel; Rational Bubbles; CIENCIAS SOCIAIS APLICADAS::ECONOMIA; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::METODOS QUANTITATIVOS EM ECONOMIA